1993
DOI: 10.1152/jappl.1993.74.2.934
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stimulation-induced changes in mitochondria and performance in rat skeletal muscle

Abstract: Chronic low-frequency (10-Hz) electrical stimulation was used to investigate mitochondrial biogenesis in rat tibialis anterior muscle. Succinate dehydrogenase and citrate synthase were used as mitochondrial enzymes, and cardiolipin (CL) was used as a phospholipid index of the inner membrane. Stimulation was via the peroneal nerve (24 h/day) for 1, 2, 3, 5, 7, 10, 14, 21, and 28 days (n = 3-9 rats/day). After each period, endurance performance was evaluated in situ. The contralateral side (CON) served as contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
60
0

Year Published

1996
1996
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(70 citation statements)
references
References 0 publications
10
60
0
Order By: Relevance
“…It has been well established that skeletal muscle mitochondrial content is particularly sensitive to changes in contractile activity (1,3,7,14,26,27). In the present study, we show that chronic stimulation results in an increase in whole muscle mitochondrial content (Fig.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…It has been well established that skeletal muscle mitochondrial content is particularly sensitive to changes in contractile activity (1,3,7,14,26,27). In the present study, we show that chronic stimulation results in an increase in whole muscle mitochondrial content (Fig.…”
Section: Discussionsupporting
confidence: 74%
“…Constant, Quebec, Canada) were given food and water ad libitum. The implantation of electrodes and the chronic stimulation procedures were performed as previously described (26) and were approved in accordance with the regulations of the York University Animal Care Committee. Briefly, rats were anesthetized with an intraperitoneal injection of xylazineketamine (0.2 ml/g body wt).…”
Section: Methodsmentioning
confidence: 99%
“…Our data indicate a greater reliance of SS mitochondria on acidic phospholipids such as cardiolipin for import; they establish the importance of precursor-phospholipid interactions for protein import in subtypes of mammalian mitochondria; and they represent another indication that the regulation of import in these two mitochondrial subfractions differs. These data also have implications for mitochondrial biogenesis, since we have previously shown that large and rapid increases in cardiolipin content occur in muscle responding to chronic contractile activity prior to substantial increases in mitochondrial enzyme activity (36). Thus, an initial increase in cardiolipin content within the organelle could facilitate the subsequent import of proteins, particularly in SS mitochondria.…”
Section: Imf and Ss Mitochondrial Protein Respond Differently To Altementioning
confidence: 83%
“…All experiments involving animals were evaluated and approved by the York University Animal Care Committee in accordance with the regulations of the Canadian Council on Animal Care. Animals were prepared essentially as described previously (73). They were anesthetized with pentobarbital sodium (60 mg/kg), and the left common carotid artery was catheterized (PE-50) to allow us to monitor hemodynamic parameters with the use of a pressure transducer (model RS 3200, Gould, Cleveland, OH).…”
Section: Animalsmentioning
confidence: 99%